DEVELOPMENT OF TENNIS PLAYERS' TECHNICAL TRAINING - Kdirbaeva Aziza Berdibaevna (International Journal of Literature and Language Studies, 2026)
This thesis highlights methods for developing tennis players' technical preparation, the importance of the training process, and modern training tools. The role of regular exercises and an individual approach in improving the technical skills of athletes is also analyzed. The scientific work extensively covers issues of developing the technical training of tennis players and modern methods and tools used to enhance their athletic mastery. Tennis is a complex sport that requires a high level of speed, agility, strength, endurance, and the precise and effective execution of technical movements. Therefore, the proper organization and regular development of athletes' technical preparation are of great importance. The study analyzes the main elements of tennis players' technical training, including the correct grip of the racket, ball reception, passing, forehand and backhand strikes, service, and the improvement of defensive and offensive movements. It also reveals the importance of considering the age characteristics, physical fitness level, and individual capabilities of athletes during the training process. The effectiveness of using special exercises, repetitive exercises, coordination actions, and modern pedagogical technologies in developing technical training is substantiated. The scientific work also examines the role of coaches in the formation of technical skills, the psychological state of athletes, and factors ensuring stability in the competitive process. Research findings indicate that the regular improvement of technical preparation serves to enhance the quality of tennis players' play and their performance in competitions. This article is of great importance as a practical and theoretical resource for tennis coaches, athletes, and students majoring in physical education.